PENGARUH KARAKTERISTIK TATA KELOLA DAN KARAKTERISTIK PERUSAHAAN TERHADAP KEPUTUSAN PERUSAHAAN TERKAIT SUSTAINABILITY REPORTING - Mutia Rahmania; Aditya Septiani (Diponegoro Journal of Accounting, 2019)
The purpose of this study is to examine the effect of governance characteristics and firm characteristics on the company's decision to release the sustainability report separately and the company's decision to attach an external assurance statement to the sustainability report. The population in this study are companies that have been listed on the Indonesia Stock Exchange (IDX) and Bursa Malaysia. The samples used are companies in the top 100 in each country based on its market capitalization. The final samples used are 189 companies to test the dependent variable of the company's decision to release the sustainability report separately. Furthermore, the sample was further reduced to 71 companies that released the sustainability report separately to test the dependent variable of the company's decision to attach the external assurance statement to the sustainability report. The analysis of the research used is descriptive statistics and logistic regression because the two dependent variables are dummy variables. The results showed that the number of board meetings and the number of nomination and remuneration committee meetings had a significantly positive effect on the company's decision to release the sustainability report separately. Then, it was also found that the number of board meetings, the number of nomination and remuneration committee meetings, and the number of members of the nomination and remuneration committee had a significantly positive effect on the company's decision to attach the external assurance statement to the sustainability report.